STRATEGI IMPLEMENTASI PENDIDIKAN HUMANIS DI MTS WAHID HASYIM DAU MALANG - Moh Eko Nasrulloh; Yoyok Amirudin (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2019)
Indonesian society is currently experiencing humanitarian problems. In the era of globalization where technology is increasingly sophisticated which results in ease in many fields but also has a negative impact on the other side. Temporary problems encountered in the community, namely Research originated from concerns about the phenomenon of violence that occurred in the educational environment in East Java. The act of bullying in school is a disturbing thing to social values. As a description of a phenomenon, this study uses a qualitative descriptive design. Data collection was carried out in this study by observation, interviews, and documentation. The strategy for implementing humanist education at MTs Wahid Hasyim Dau is done by planning, implementing and evaluating educational programs in schools and management. Implementation strategies for implementing character education in schools, with 4 forms, namely: 1. Integration of values and ethics on subjects. 2. Internalization of the positive values instilled by all school members. 3. Habit and training, giving examples and role models. 4. Creation of atmosphere in school and culture. While efforts to minimize dehumanization are carried out by establishing the principle of family, cooperation, and intimacy and providing self-awareness / self-introspection, tausiah. The implementation of humanist education in learning forms integration with learning, school management, and extracurricular activities. The implementation of humanist education at Dau carries out some aspects of the theory of Paul Freire, but efforts to realize humanist education with consideration to the problems and needs of the era are good. Keywords: Strategy, Implementation, Education, Humanism